2015
DOI: 10.1242/jcs.168682
|View full text |Cite
|
Sign up to set email alerts
|

Probing microtubule polymerisation state at single kinetochores during metaphase chromosome motion

Abstract: Kinetochores regulate the dynamics of attached microtubule bundles (kinetochore-fibres, K-fibres) to generate the forces necessary for chromosome movements in mitosis. Current models suggest that poleward-moving kinetochores are attached to depolymerising K-fibres and anti-poleward-moving kinetochores to polymerising K-fibres. How the dynamics of individual microtubules within the K-fibre relate to poleward and anti-poleward movements is poorly understood. To investigate this, we developed a live-cell imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 38 publications
(57 reference statements)
1
34
0
Order By: Relevance
“…However, recent live-cell imaging in human cells (Armond et al, 2015) and electron microscopy studies (VandenBeldt et al, 2006) has demonstrated that both P and AP K-fibres are incoherent, i.e. contain both polymerising and depolymerising microtubules, with a small polymerisation bias towards the AP K-fibre (Armond et al, 2015) (Fig. 2B).…”
Section: Coordinating Microtubule Dynamicsmentioning
confidence: 98%
See 3 more Smart Citations
“…However, recent live-cell imaging in human cells (Armond et al, 2015) and electron microscopy studies (VandenBeldt et al, 2006) has demonstrated that both P and AP K-fibres are incoherent, i.e. contain both polymerising and depolymerising microtubules, with a small polymerisation bias towards the AP K-fibre (Armond et al, 2015) (Fig. 2B).…”
Section: Coordinating Microtubule Dynamicsmentioning
confidence: 98%
“…Experiments using fluorescent EB1 (also known as MAPRE1, a microtubule polymerisation marker) provided evidence that this bias is indeed strong, with high levels of polymerisation at the AP kinetochore relative to the P kinetochore (Tirnauer et al, 2002). However, recent live-cell imaging in human cells (Armond et al, 2015) and electron microscopy studies (VandenBeldt et al, 2006) has demonstrated that both P and AP K-fibres are incoherent, i.e. contain both polymerising and depolymerising microtubules, with a small polymerisation bias towards the AP K-fibre (Armond et al, 2015) (Fig.…”
Section: Coordinating Microtubule Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preferential binding is statistically significant (p<0.02, two-sided Z-test), 1 yet small, presumably because leading and trailing kinetochores have a mixture of both polymerizing and 2 depolymerizing MTs (Armond et al, 2015). This differential binding of NDC80 provides an explanation 3 for the higher detachment rate of depolymerizing microtubules from kinetochores in vitro (Akiyoshi et al, 4 2010), and may give insight into the nature of kMT attachments (Dumont et al, 2012).…”
mentioning
confidence: 99%